The Development of the Turkish Craving for Internet Gaming Scale (CIGS): A Validation Study - Savci, Mustafa; Griffiths, Mark D. (Springer, 2022)
As the use of digital technology has increased, abuse and addiction to technology have been identified among a minority of users. In the mid-1990s, the concept of internet addiction was first used. Today, almost every digital technology use has been claimed to have a minority of disordered users. One key aspect of addictive substance behaviors is craving. Craving is also an important component of behavioral addictions including digital technology disorders such as Internet Gaming Disorder. The aim of the present study was to develop the Turkish version of the Craving for Internet Gaming Scale (CIGS) via an adaptation of the Penn Alcohol Craving Scale (PACS). The present study comprised 368 adolescents from four different samples. The measures used included the Craving for Internet Gaming Scale, Digital Game Addiction Scale, and Brief Self-Control Scale. The structural validity of CIGS was investigated with Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and criterion validity. The reliability of CIGS was evaluated using Cronbach alpha internal consistency reliability coefficient and corrected item total correlation coefficients. As a result of EFA, it was found that the five-item CIGS had a single-factor structure. The unidimensional CIGS obtained as a result of EFA was tested with CFA. As a result of CFA, the unidimensional structure of CIGS was confirmed in two different samples. Criterion validity of CIGS was assessed via digital gaming addiction, self-discipline, impulsiveness, daily internet gaming duration, and internet gaming history. As a result of criterion analysis, CIGS was associated with these variables in the expected direction. Finally, according to reliability analysis, the CIGS was found to be a reliable scale. When validity and reliability analysis of the CIGS are considered as a whole, it is concluded that the CIGS is a valid and reliable scale that assesses craving for internet gaming.
Keywords: Online gaming; Internet gaming disorder; Craving; Internet gaming craving; Online gaming addiction